PLANTS AND FOODS THAT DILUTE BLOOD AND WORSEN BLOOD RHEOLOGY IN ARTERIAL HYPERTENSION - Soliev Alisher Urokovich; Urokova Dilshoda Alisher kizi (Journal of Science in Medicine and Life, 2024)
Thick blood worsens the delivery of oxygen, hormones, and nutrients to cells. It can lead to heart attacks, strokes, and kidney damage, so doctors prescribe anticoagulants to reduce its viscosity. However, there is a list of foods that naturally thin the blood. Research shows that some foods effectively improve circulation and reduce the risk of vascular problems, which can negatively affect the heart, brain, intestines, eyes, and other organs.